The End of Leadership - Kellerman, Barbara (New York Harper Collins, 2012)
From one of the pioneers in the field of leadership studies comes a provocative reassessment of how people lead in the digital age: in The End of Leadership, Barbara Kellerman reveals a new way of thinking about leadership?and followership?in the twenty-first century. Building off of the strengths and insights of her work as a scholar and a teacher, Kellerman critically reexamines our most strongly-held assumptions about the role of leadership in driving success. Revealing which of our beliefs have become dangerously out-of-date thanks to advances in social media culture, she also calls into question the value of the so-called ?leadership industry? itself. Asking whether leadership can truly be taught, Kellerman forces us to think critically and expansively about how to thrive as leaders in a global information age.
Includes Index
Keywords: Leadership